2021
DOI: 10.1001/jamaophthalmol.2020.5972
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Home-Printable Vision Screening Test for Telemedicine

Abstract: Crossland et al. Remote vision testing. Key PointsQuestion: Can a, printed vision chart posted to people with eye disease measure their vision accurately?Findings: In this study of 50 control subjects and 100 ophthalmology outpatients, Bland-Altman analyses showed excellent repeatability of the home acuity test, and good agreement with the last recorded clinic visual acuity.Meaning: These findings suggest a printed chart can be used to measure visual acuity at home by ophthalmology patients

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 26 publications
4
27
0
1
Order By: Relevance
“…The mean difference in VA for their patients was −0.10 logMAR (SD 0.17, range −0.5 to 0.3) with the office test indicating better vision than home assessment. 7 In contrast, our study found similar results between the tests (mean difference −0.02 logMAR, SD 0.15). A limitation of their study was the long duration between office and home assessment (mean of 12 months, range 1–69 months), during which vision may have deteriorated.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The mean difference in VA for their patients was −0.10 logMAR (SD 0.17, range −0.5 to 0.3) with the office test indicating better vision than home assessment. 7 In contrast, our study found similar results between the tests (mean difference −0.02 logMAR, SD 0.15). A limitation of their study was the long duration between office and home assessment (mean of 12 months, range 1–69 months), during which vision may have deteriorated.…”
Section: Discussionsupporting
confidence: 67%
“…Our study found similar results compared to Crossland et al’s paper, which also evaluated office-based versus home self-assessment using a printable home vision test. 7 They evaluated patients from adult strabismus and low vision clinics. The mean difference in VA for their patients was −0.10 logMAR (SD 0.17, range −0.5 to 0.3) with the office test indicating better vision than home assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Capacity is more severely limited by social distancing as all patients will attend clinics accompanied by an adult. Although a gamut of teleophthalmology solutions, including remote vision testing, has been trialled and rolled out with moderate degrees of success in adult ophthalmology subspecialties (Bourdon et al 2020;Gillam et al 2020;Kang et al 2020;Kilduff et al 2020;Mintz et al 2020;Crossland et al 2021;Faes et al 2021), it may be more difficult to adapt these to the paediatric population. Our paper reveals a striking statistic: when triaging cancelled outpatient appointments during the first peak at AHCH, only 6.8% were deemed to be suitable for a telephone or video consultation.…”
Section: Discussionmentioning
confidence: 99%